1999
DOI: 10.1111/j.1559-1816.1999.tb01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of African Americans Toward Participation in Medical Research

Abstract: The underrepresentation of African Americans in medical research is problematic for several reasons, including disparities in health outcomes, differences in metabolism of pharmacological agents, and accurate assessment of health needs and costs. This paper investigates factors contributing to African Americans' lower likelihood of consenting to participation in medical research. In Study 1, three focus groups were conducted to assess concerns about research participation and to generate further hypotheses for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
0
34
1
Order By: Relevance
“…Previous studies have noted that blacks were less likely to participate in clinical research. 5,6,21,29 With blacks also being at a higher risk for disease conditions and discrimination due to outside factors such as socioeconomic status, 30-32 understanding the link among health care service utilization, future participation in medical research, and race is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have noted that blacks were less likely to participate in clinical research. 5,6,21,29 With blacks also being at a higher risk for disease conditions and discrimination due to outside factors such as socioeconomic status, 30-32 understanding the link among health care service utilization, future participation in medical research, and race is of critical importance.…”
Section: Discussionmentioning
confidence: 99%
“…5-9 Medical mistrust is an important concept to understand, especially as it relates to health care services and medical research. Historical occurrences of abuse in medical research, as well as personal experiences of discrimination within medical care and society, have been well documented, and have been highlighted as potential sources of medical mistrust.…”
Section: Racial Differencesmentioning
confidence: 99%
“…Likewise, discussion of the Tuskegee Syphilis Study revealed concerns by the black community that researchers would take advantage of them to obtain meaningful results for scientific publications. 1,3 Research by Mason 4 , Stahl and Vasquez 5 , and Moreno-John, Gachie, Fleming, et al 8 suggests similar findings. In a review of these studies, African Americans consistently reported a lack of trust in research and research personnel.…”
mentioning
confidence: 83%
“…2 This lack of participation has been attributed to a variety of factors that include a mistrust of the predominately white research establishment with its well-documented history of medical abuse, differing cultural attitudes and beliefs towards research and illness, isolation of older individuals, and a lack of education about the purpose of research in general and the informed consent process in particular. 1, 35 …”
mentioning
confidence: 99%
“…Men recruited for the study were skeptical of couples interventions, as has been noted (Doss, Atkins, & Christensen, 2003), and involving mentors who believed in and were committed to the inclusion of fathers in the prenatal intervention was essential. So too was the cultural competence of mentors, who understood the challenges faced in the community by African American children and parents and who could connect with parents in these realities (Armstrong, Crum, Rieger, Bennett, & Edwards, 1999). Future research would benefit from further examination of mentor background and competencies.…”
Section: Discussionmentioning
confidence: 99%